Exploring the relationship between meaning in life and subjective well-being among older adults in China - Xu, Mengze; Lachica, Toni-An B.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
The accelerating aging of China’s population has raised significant attention to the mental health and well-being of older adults. This descriptive correlational study aimed to examine the levels of meaning in life and subjective well-being among a select group of older adults in Chengde City, China, and to explore the relationship between these two constructs. A total of 170 participants were recruited using purposive sampling, and data were collected using an online survey comprising a demographic questionnaire, the Meaning in Life Questionnaire–Chinese Version (MLQ-C), and the Personal Well-Being Index–Chinese Version (PWI-C). Statistical analyses indicated that participants reported generally high levels of meaning in life and subjective well-being. Significant differences in meaning in life were found based on gender and education level, whereas subjective well-being did not significantly differ across demographic variables. A moderate positive correlation (r = .55, p < .001) was observed between meaning in life and subjective well-being. These findings underscore the importance of fostering a sense of meaning in life to promote the mental health and quality of life among older adults. Practical implications for nursing practice, community interventions, and future research directions are discussed, highlighting the need for targeted strategies to enhance life meaning and well-being in aging populations.